2020
DOI: 10.5796/electrochemistry.19-00074
|View full text |Cite
|
Sign up to set email alerts
|

Improved Electrochemical Properties of LiCoO<sub>2</sub> via Ni, Mn Co-doping from LiNi<sub>0.8</sub>Co<sub>0.1</sub>Mn<sub>0.1</sub>O<sub>2</sub> for Rechargeable Lithium-ion Batteries

Abstract: composite was prepared by the combination of mechanical ball milling and heat treatment. The as-prepared LiCoO 2 /LiNi 0.8 Co 0.1 Mn 0.1 O 2 composite was characterized by X-ray diffraction, scanning electron microscopy, and energy-dispersive X-ray Spectroscopy. The LiCoO 2 /LiNi 0.8 Co 0.1 Mn 0.1 O 2 composite was utilized as cathode material for lithium-ion batteries. Compared with the milled LiCoO 2 /LiNi 0.8 Co 0.1 Mn 0.1 O 2 composite, the LiCoO 2 /LiNi 0.8 Co 0.1 Mn 0.1 O 2 composite after heat treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…The performance of the initial charge-discharge is related to the surface structure of the material. [29][30][31] Thus, this shows that the Rocksalt phase contributes to the cycle of the materials.…”
Section: Analysis and Resultsmentioning
confidence: 75%
“…The performance of the initial charge-discharge is related to the surface structure of the material. [29][30][31] Thus, this shows that the Rocksalt phase contributes to the cycle of the materials.…”
Section: Analysis and Resultsmentioning
confidence: 75%
“…But interestingly, NCM-Co16 with the highest Co content at a high cutoff voltage (4.6 V) had the best output capacity during discharge and the highest initial Coulomb efficiency. The performance improvement in initial charge–discharge was related to the modification of the surface structure; ,, hence, it was indicated that the increase of Co content was able to improve the surface structural stability of high-nickel layered materials under a high voltage. This corresponds to the morphological changes in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…Thereinto, Mn 4+ exists to compensate for Ni 2+ and make the comprehensive valence state of transition-metal ions to +3, thus stabilizing the layered structure . The redox of Ni ions vs Ni 2+ /Ni 4+ shows their capacity; hence, increasing the content of Ni is the most effective way to improve the energy density of ternary cathode materials. However, blindly reducing the Co content and increasing the Ni content to reduce the cost and increase the capacity will make the lattice structure of the material extremely unstable.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11] The shortcomings of NCM811 have been addressed by a number of novel modifications. [12][13][14][15][16][17][18][19] However, blind modification with an insufficient understanding of the defects is of no value to the improvement of the cycling performance of NCM811.…”
mentioning
confidence: 99%